1998
DOI: 10.1109/23.682440
|View full text |Cite
|
Sign up to set email alerts
|

Surface polishing of GSO scintillator using chemical process

Abstract: A Ce doped Gd,SiO, (GSO) single crystal is an excellent scintillator featuring a large light output, a short decay constant and a high absorption coefficient. It was shown in our previous studies that the surfaces of the scintillator should be polished to get scintillation light output efficiently especially for long and narrow scintillators. Therefore, we newly developed a chemical process to polish the GSO crystal. The surface of the GSO crystal was found to become smooth when it was etched using anhydrous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Chemical etching is known to be helpful in improving the performance characteristics of scintillating crystals [22][23][24]. It gives a rough surface finish comparing with the mechanical polish [22] improving the light collection in the readout configuration when there is no optical contact between the sample and detector [24].…”
Section: Resultsmentioning
confidence: 99%
“…Chemical etching is known to be helpful in improving the performance characteristics of scintillating crystals [22][23][24]. It gives a rough surface finish comparing with the mechanical polish [22] improving the light collection in the readout configuration when there is no optical contact between the sample and detector [24].…”
Section: Resultsmentioning
confidence: 99%
“…All crystals were 3 3 3 mm in size except for the 0.75 mol% samples, which were 3 3 2.5 mm , and had chemically etched surfaces [22]. Since crystal size affects the light collection efficiency and, therefore, the measured scintillation light output and energy resolution, we chose these small-size crystals to facilitate the comparative assessment of intrinsic scintillator characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…We use R as an abbreviation of a crystal element with rough surface and C with chemically etched surface. It is reported that the R and C have 411 nm and 382 nm roughness, 293 nm and 1045 nm waviness in their surface, respectively [12]. R has a property that it makes incident photons out to any other sides of coming side because rough surface diffuses the photons while C tends to transmit most of them to the same direction [13].…”
Section: B Parameters For Optimization Of the Crystal Blockmentioning
confidence: 99%